Effects of X-ray and electron beam irradiation on wine quality: Emphasizing phenolic compounds and aroma profiles - Weikang Ding; Qian Tu; Xuexue Xi; Xiaojie Wu; Junqing Bai; Shuang Liu; Junjun Li; Chunlong Yuan (Food Chemistry: X)
The content of flavor compounds in wine is limited by factors such as climate warming and the resistance of cell walls to maceration. This study used X-rays (ionizing radiation) and electron beams (particle radiation) at 0.5, 2, and 7 kGy for grape pre-treatment before winemaking. Scanning electron microscopy showed varying degrees of grape skin damage. Results indicated irradiation significantly enhanced phenolic compound extraction, with DPPH and ABTS scavenging activities increasing by up to 38.98 % and 38.70 %. Wines treated with 0.5 kGy electron beams exhibited the highest levels of esters and higher alcohols, enhancing fruity aromas. Irradiation reduced C6 compound content, decreasing green notes and improving color and complexity scores. This study demonstrates that X-ray and electron beam irradiation significantly enhance phenolic and aromatic compound extraction in wine, showing the potential of irradiation technology in the wine industry.